Molecular detection of the Hepatitis C virus genotypes circulating among both sexes of Khyber Pakhtunkhwa, Pakistan - Waqar, Muhammad; Rehman, Habib Ur; Wasim, Muhammad; Khan, Asad Ullah; Ahmad, Tauseef; Akbar, Noor Ul; Zeb, Mubarak; Khan, Effa; Sheikh, Aisha; Noor, Agha Asad; Ali, Niyaz; Shah, Tariq; et al. (Asian Journal of Medical Sciences, 2014)
Background: Hepatitis C Virus (HCV) is the major cause of viral hepatitis. A few studies revealed that HCV genotypes; 3a, 3b, 1a and 1b are the most common genotypes found in the general population of Khyber Pakhtunkhwa. Aims and Objective: The current is designed to find out the prevalence of HCV genotypes among both sexes of Khyber Pakhtunkhwa. Study Methods: The present study was carried out in various area of Khyber Pakhtunkhwa during the period of July, 2012 to July, 2013. All the HCV positive samples were genotyped. The statistical analysis of the data was done by using Statistix 9.0 software. Result: The results showed that the male, 53.1% (n=340) were more infected as to female, 46.8% (n=300). The overall result shows that in male patients; the high number of cases (216) was reported of 3a whereas the lowest cases (8) were reported of 1b. The mixed genotype is recorded in 8 patients. In female patients; the 3a is detected in 170 patients whereas the lowest cases of genotype (3b) are reported in 5 patients. In female patients; the mixed genotype is reported in 11 patients. Conclusion: From the present study, it was concluded that the male were more infected as compare to female and the genotype 3a was the most common genotype in both sexes. Asian Journal of Medical Science, Volume-5(3) 2014: 72-76 http://dx.doi.org/10.3126/ajms.v5i3.9449